Design and fabrication of display unit for exploded components of single cylinder 4 stroke engine - Mohamad Faza Firdaus, Mohd Rashid (2012)
This report shows the design and fabrication of the display unit for exploded component of single cylinder four stroke engine. The objective of the report is to develop the procedures to design and fabricate the display unit in exploded view for use of in teaching plan. Design generation is showed and solid three dimensional structure model was developed with the solid work software. Material selection and the reason behind the selection are shown based on criteria predetermined. Based on the selection, acrylic and steel are selected. This project is difficult to make because it is hard to find the references and information of similar project and it’s the method to arrange part of the engine. The results show each part of component can be successfully assembled.